THE EFFECTS OF SMALL AMOUNT OF HYDROGEN ADDITION ON PERFORMANCE AND EMISSIONS OF A DIRECT INJECTION COMPRESSION IGNITION ENGINE - (:unkn) unknown (VINCA INST NUCLEAR SCI, 2018)
In this study, the effects of small amount of hydrogen addition into the intake of compression ignition engine on the performance and emissions characteristics of single cylinder, air cooled, direct injection, compression ignition engine were experimentally investigated. An electrolysis unit was built to produce hydrogen peroxide, which was then fed into the intake manifold of the compression ignition engine. The compression ignition engine was tested with different amount of hydrogen (0.15, 0.30, 0.45, and 0.60 Lpm) at different engine load (5%, 25%, 50%, 75%, and full load) and the constant speed, 2200 rpm. Experimental results show that increasing amount of hydrogen into the inlet air resulted to decrease in brake specific fuel and energy consumption while resulted to increase brake thermal efficiency at all load conditions due to uniformity in mixture formation and higher flame speed of hydrogen. The better combustion improved exhaust emission. However, exhaust temperature only increased for 0.6 Lpm hydrogen addition into the inlet air at higher loads resulting in higher quantity of nitrogen oxides formation.
Keywords: Diesel engine; electrolysis; hydrogen; engine performance; exhaust emissions; DI DIESEL-ENGINE; FUEL-INJECTION; DUAL FUEL; COMBUSTION; OIL; SYSTEM